Investigating the carbonation and mechanical performance of reactive MgO cement based concrete mixes - Unluer, Cise (2019)
Carbonation governs the microstructure and the overall mechanical performance of mixes involving MgO cements as the main binder. Aggregate grading has a significant influence on the carbonation process due to the different particle arrangements that determine the porosity and permeability of the resulting formulations. This work investigates the effect of aggregate particle size distribution on the carbonation of blocks containing reactive MgO. Samples containing four different aggregate profiles were subjected to accelerated carbonation at 20% CO2 concentration for up to 28 days. While the influence of gap grading on strength development was not very pronounced, mixes with the lowest initial porosity indicated the greatest increase in density at the end of 28 days. This also translated into the highest strength results obtained due to the formation of hydrated magnesium carbonates, reaching 10 MPa only after 1 day of carbonation. The porosity values measured before carbonation were inversely correlated with the corresponding densities and final strengths of each mix. An inverse correlation between porosity and permeability values before carbonation led to the conclusion that the connectivity of pores rather than the total pore volume controls the carbonation reaction. Mixes with higher initial permeabilities achieved the highest strengths, proving that the extent of CO2 diffusivity is mainly dependent on pore connectivity.